UTILIZING EGGSHELL WASTE AS A MEDIUM FOR MOSAIC ART LEARNING IN PRIMARY EDUCATION - Septi Afriani; Athian, Muhammad Rahman (Universitas Negeri Semarang, 2026)
The research is based on the fact that SD Negeri 1 Nangkasawit in learning fine arts has produced mosaic works, but the works produced have never used eggshell waste as a medium for making fine art. Therefore, the author collaborated with teachers to use different media by utilizing eggshell waste. The problems studied in this study are: (1) What is the learning process of using eggshell waste in making mosaic art in Class IV of SD Negeri 1 Nangkasawit?; (2) What are the results of the use of eggshell waste in mosaic art in Class IV of SD Negeri 1 Nangkasawit?. The method used is research with a qualitative approach that is descriptive, which is more about displaying the description of words than numbers. Therefore, the techniques used in the effort to obtain data in the field are by using observation, interviews, and documentation. The results of the research on the use of eggshell waste in making mosaic art for Grade IV students of SD Negeri 1 Nangkasawit reached a total score of 914 with an average score of 83 and was included in the good category. Of the total, there are students who do not go to school when making mosaic art, so there are only 11 mosaic works made by students. There were 2 students or 18% who got a score with a very good category, 5 students or 46% who got a score with a good category, and 4 students or 36% who got a score with a good category. Suggestions that can be put forward are: (1) Teachers are advised to be able to creatively utilize the media around them in learning fine arts; (2) Schools should provide fine arts learning facilities and provide art spaces.